Maternal Cardiac Output Changes After Crystalloid or Colloid Coload Following Spinal Anesthesia for Elective Cesarean Delivery: A Randomized Controlled Trial - McDonald, Sarah; Fernando, Roshan; Ashpole, Keri; Columb, Malachy (Anesthesia and analgesia, 2011)
Minimizing hypotension associated with spinal anesthesia for cesarean delivery by administration of IV fluids and vasopressors reduces fetal and maternal morbidity. Most studies have concentrated on noninvasive systolic blood pressure (SBP) measurements to evaluate the effect of such regimens. We used a suprasternal Doppler flow technique to measure maternal cardiac output (CO) variables in parturients receiving a phenylephrine infusion combined with the rapid administration of crystalloid or colloid solution at the time of initiation of anesthesia (coload). We hypothesized that a colloid coload compared with a crystalloid coload would produce a larger sustained increase in CO and therefore reduce vasopressor requirements. We recruited 60 healthy term women scheduled for elective cesarean delivery under spinal anesthesia for this randomized double-blind study. Baseline heart rate, baseline SBP, and CO variables including stroke volume, corrected flow time, and contractility were recorded in the left lateral tilt position. At the time of spinal injection, subjects were allocated to receive a rapid 1-L coload of either 6% w/v hydroxyethyl starch solution (HES) or Hartmann (crystalloid) solution (HS). A phenylephrine infusion was titrated to maintain maternal baseline SBP. CO was measured at 5-minute intervals for 20 minutes after initiation of spinal anesthesia. The primary outcome, CO, was compared between groups, as were secondary outcomes: phenylephrine dose and maternal hemodynamic and fetal outcome data. Maternal demographics, surgical times, and fetal outcome data were similar between groups. There were no significant differences between groups in any measured CO variable at any time point. CO was transiently higher than baseline at 5 minutes in the HS group and at 5 and 10 minutes in the HES group (range, 0.13-1.74 L/min); the overall mean difference in CO between crystalloid and colloid over the study period was 0.06 L/min (95% confidence interval: -0.46 to 0.58). Stroke volume was higher than baseline in both groups throughout; peak velocity was consistently higher than baseline only in the HES group; and corrected flow time increased in both groups; the effect was transient in the HS but sustained in the HES group. Heart rate was not different at any time point within or between groups but did decrease over time. The total phenylephrine dose from time of spinal anesthesia to delivery was similar between groups. We found no difference in CO in women randomized to colloid or crystalloid coload. In addition, there were no differences in vasopressor requirements or hemodynamic stability. We conclude that there is no advantage in using colloid over crystalloid when used in combination with a phenylephrine infusion during spinal anesthesia for elective cesarean delivery.